The Role of Nurses in Patient Safety Culture Implementation in the Neonatal and Pediatric Care Intensive Unit - Santi Anugrahsari; Elys Yulianti; Shirley Eleonora Gusmariny Teterissa; Dietha Kusumaningrum; Safira Cantika Desra; Sumidjatun Sumidjatun (CV. Global Health Science Group, 2025)
Patient safety culture plays a vital role in improving the quality of health services, especially in the Neonatal and Pediatric Intensive Care Unit that serves critically ill patients. Evaluation of patient safety culture in NICU and PICU nurses at RSUD X is essential to understand the extent of compliance and challenges in its implementation. This study analyzed patient safety culture in the NICU and PICU of RSUD X from the perspective of nurses using the Hospital Survey on Patient Safety Culture (HSOPSC) version 2.0, developed by the Agency for Healthcare Research and Quality (AHRQ). This study used a descriptive cross-sectional design involving 52 nurses. Data were collected by filling out the HSOPSC AHRQ 2.0 questionnaire, which consisted of 12 composites that described different aspects of patient safety culture. The HSOPSC 2.0 (AHRQ) instrument was used because its validity and reliability have been tested in measuring patient safety culture globally. The data were analyzed descriptively to identify the dimensions with the highest and lowest values. The survey results suggested that the patient safety culture in nurses working in the NICU and PICU had several strong aspects, including teamwork (77.54%), communication about errors (72.43%), and managerial support (71.15%). However, other elements must be considered more intensively, which are responses to errors (56.24%) and staffing (42.9%). Although the patient safety culture in the NICU and PICU of RSUD X has proven good in some aspects, improvement in incident reporting and workload management is required.